Hepatocellular Carcinoma 2019
DOI: 10.15586/hepatocellularcarcinoma.2019.ch1
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Origin of Hepatocellular Carcinoma

Abstract: Molecular features of hepatocellular carcinoma affect patient prognosis and treatment efficiency. This chapter provides an overview of the relevant studies conducted to identify the cell of origin of hepatocellular carcinoma with a special focus on the controversy of hepatocytes versus hepatic progenitors as the main tumor-initiating cell. Furthermore, we introduce the concept of cancer stem cells (CSCs) and highlight recent publications covering this topic in relation to liver cancer. More precisely, we conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 171 publications
(196 reference statements)
0
8
0
Order By: Relevance
“…The cellular compartment giving rise to the tumor-initiating cell in HCC is under intense debate, and either progenitor/stem cells or differentiated liver cells could be responsible. Experimental evidence indicates a model where every cell can be a key player [123]. There is profound inter-tumoral heterogeneity in HCC with respect to genetic profiles, allowing for the discrimination of at least two genetic/molecular subgroups, as described above [7,124], and transcriptional profiling can distinguish different prognostic subgroups.…”
Section: Stem Cells In the Normal Livermentioning
confidence: 99%
“…The cellular compartment giving rise to the tumor-initiating cell in HCC is under intense debate, and either progenitor/stem cells or differentiated liver cells could be responsible. Experimental evidence indicates a model where every cell can be a key player [123]. There is profound inter-tumoral heterogeneity in HCC with respect to genetic profiles, allowing for the discrimination of at least two genetic/molecular subgroups, as described above [7,124], and transcriptional profiling can distinguish different prognostic subgroups.…”
Section: Stem Cells In the Normal Livermentioning
confidence: 99%
“…The functional LCSC marker CD24 was found to drive liver CSC genesis through STAT3-mediated Nanog regulation (Lee et al, 2011). The IL-6/STAT3 signaling pathway was proposed to be related to liver inflammation and liver regeneration (Schneller and Angel, 2019), and the mechanism is to maintain the liver CSC population through interaction with the TGF-β signaling pathway (Tang et al, 2008). A recent study demonstrated that the IL6/STAT3 signaling cascade mainly causes CD133 + enrichment in liver cancer (Won et al, 2015).…”
Section: Stat3 Signalingmentioning
confidence: 99%
“…Among these were 0.84 million new liver cancer patients and 0.78 million new deaths due to liver cancer. An analysis of 38 specific cancers detailed in GLOBOCAN 2018 revealed that liver cancer is the third most fatal cancer, 1 and hepatocellular carcinoma (HCC) is the main type of liver cancer 2 . Viral HCC is caused by chronic infection with the hepatitis B or hepatitis C virus 2 and was predominant in Western countries and Japan until the late 1990s.…”
Section: Introductionmentioning
confidence: 99%